Orthopedic Manifestations of Bruck Syndrome: A Case Series with Intermediate to Long-term Follow-Up - Adolfredo Santana; Geovanny Oleas-Santillán; Jeanne M. Franzone; L. Reid Nichols; J. Richard Bowen; Richard W. Kruse (Case Reports in Orthopedics)
The aim of this study was to evaluate the association of contractures, fractures, and deformities in four patients with Bruck syndrome treated in our facility. Data were collected from medical records, radiographs, dual-energy X-ray absorptiometry (DEXA) scans, genetic tests, and gait analysis. All had contractures at birth and genotypic findings including mutations in PLOD2 or FPKB10. Three cases were treated with bisphosphonates with improvement in bone density verified by DEXA. In Bruck syndrome, orthopedic deformities include the following sequential aspects: contractures, characterized by upper and lower extremity contractures such as clubfeet; fractures, characterized by multiple diaphyseal fractures in the long bones of the extremities; and deformities, characterized by malalignment of extremities and the spine. Physical therapy and bracing proved helpful for the contractures to try to stop progression. Bone fragility needs to be considered when deciding to attempt cast correction. Surgeries in the soft tissues can be performed to retain joint movement. In fractures with angulation, intramedullary nail fixation was useful, and in cases without deformity, casting alone was successful. We suggest monitoring the bone density with DEXA, nutrition support with vitamin D and calcium, and treatment with bisphosphonates. Spine deformities were successfully treated by spinal fusion and instrumentation.